(untitled) (Semiárida, 2023)
The objective of this work was to evaluate the effect of different sources of phosphorus and its interaction with nitrogen, on the yield, quality, and nutrient extraction of the wheat crop. The field experiment was carried out on an entic Haplustol, in which 8 fertilization treatments (T) were established. T 1 corresponds to the control (without adding P), in T 2, 3, 4, and 5, 18,3 kg.ha-1 of P was applied. T 6, 7, and 8 correspond to fertilizer additions at recommended rates of 30 kg.ha-1 which implies the application of 5,25 kg of P.ha-1. Two nitrogen management procedures were established in divided plots: with and without fertilization. In all the treatments with phosphorus, the addition of N presented statistically significant differences in yield. The WUE was higher in those treatments whose fertilizers have a balanced formulation of nutrients. No significant differences in protein concentration were found. T 2, 3, 4, and 5 presented a positive balance between the P applied with fertilizer and extracted in the grain, T 6, 7, and 8 had a negative balance, while T 1 (control) was the worst situation.